Analysis of Recreational Sports on Intrinsic Motivation to Write a Thesis in Final Semester Sports Science Students - Amirul Rosyid; Sahri Sahri (Journal La Sociale, 2026)
This study aims to examine the relationship between recreational exercise and intrinsic motivation in final year students of the Sport Science Study Program, Semarang State University, class of 2022, in completing their theses. Using a quantitative correlational approach with a descriptive design, a sample of 23 students was drawn through purposive sampling, and data were collected via the IPAQ short form questionnaire for physical activity and the IMI for intrinsic motivation. Analysis included normality, linearity, and Spearman correlation tests using SPSS 26. The results showed a "high" level of physical activity (average 1637,348 MET-minutes/week), "fair" intrinsic motivation (average 5.67/7), an abnormal distribution of physical activity (sig. <0.05), normal motivation (sig. >0.05), a linear pattern (sig. 0.509>0.05), but no significant correlation (sig. 0.874>0.05). In conclusion, the frequency of recreational exercise was not significantly related to increased intrinsic motivation for the thesis, likely due to the homogeneity of the sample. The frequency of recreational exercise was not significantly related to increased intrinsic motivation for the thesis, possibly due to the homogeneity of the sample.